1991
DOI: 10.1111/j.1600-0668.1991.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Transients: A Model for Heat Diffusion through the Skin, Thermoreceptor Response and Thermal Sensation

Abstract: A model based on heat diffusion through the skin is developed for the dynamic response of cutaneous thennoreceptors w temperature stimuli at the skin surjiace. It is applied w various neurophyswlogical exper'ments with good results. The model is then extended w sensation and a set of psychophysical experiments on human sub jects is examined and compared with the model predic- tions. A h g e t h q in terms of both the neurophysiological response and the sensation response, this model gives good agreement zoith … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 8 publications
(12 reference statements)
2
71
0
Order By: Relevance
“…The static part of the thermoreceptor response depends upon temperature of thermoreceptors. Also, the dynamic part of the thermoreceptor response is proportionally related to temperature change rates at the depth of the thermoreceptors, dT/dt, with positive coefficients for warm receptors and negative coefficients for cold receptors [25,29,31]. On the basis of these findings, Ring and de Dear [25] developed a simple model of thermoreceptor impulse frequency and they described the response of the cold and warm receptors as follows:…”
Section: Cutaneous Thermoreceptors Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…The static part of the thermoreceptor response depends upon temperature of thermoreceptors. Also, the dynamic part of the thermoreceptor response is proportionally related to temperature change rates at the depth of the thermoreceptors, dT/dt, with positive coefficients for warm receptors and negative coefficients for cold receptors [25,29,31]. On the basis of these findings, Ring and de Dear [25] developed a simple model of thermoreceptor impulse frequency and they described the response of the cold and warm receptors as follows:…”
Section: Cutaneous Thermoreceptors Modelmentioning
confidence: 97%
“…In 1991, Ring and de Dear [25] developed a new human thermal response model on the basis of Hensel [26] findings about the transient response of cutaneous thermoreceptors. Hensel [26] identified that the thermoreceptor response should have a static part and a dynamic part.…”
Section: Cutaneous Thermoreceptors Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We are considering including the detailed skin thermoreceptor model proposed by Ring and de Dear [29] and more detailed blood ow model for the whole limb proposed by Song et al [30].…”
Section: Future Workmentioning
confidence: 99%
“…It treats the body as a whole, in terms of physiological averages and sensations, and cannot predict transient responses. More advanced models developed in recent years [7][8][9][10][11][12] can predict transient behavior, and also calculate physiological responses for multiple (six to twenty) body parts. However, they can only predict sensation at the whole-body level, and therefore have limited value for evaluating non-uniform environments.…”
Section: Introductionmentioning
confidence: 99%